The Influence of TikTok Affiliate Digital Marketing Strategy on Generation Z Purchase Intentions in Jakarta, Indonesia - Azmi, Nurul; Afriyani, Tri; Kurniaty, Dewi (Golden Ratio of Marketing and Applied Psychology of Business, 2025)
This study aims to examine the influence of TikTok affiliate digital marketing strategies on the purchase intentions of Generation Z in Jakarta. To examine purchase intentions through TikTok affiliate marketing among Generation Z in Jakarta, variables such as perceived usefulness, trust, promotion, consumer feedback, and social impact were utilized. A quantitative method was employed by distributing questionnaires, and the data were examined using multiple linear regression analysis. The results indicate that social impact and consumer feedback have a positive and significant influence on purchase intentions. The implications of this research suggest that to enhance the purchase intentions of Generation Z in Jakarta, businesses and affiliate partners need to focus on consumer feedback or positive reviews from previous customers. Furthermore, Generation Z tends to place greater trust in recommendations from close connections such as friends, family, and relatives. To boost the purchase intentions of Generation Z in Jakarta, affiliate partners can create content highlighting positive customer reviews or businesses can collaborate with micro-influencers to build closer connections with the target audience.